2005
DOI: 10.1093/ptj/85.2.134
|View full text |Cite
|
Sign up to set email alerts
|

Testing Functional Performance in People With Parkinson Disease

Abstract: Background and Purpose. Although the Unified Parkinson's Disease Rating Scale (UPDRS) is the most common performance measure for people with Parkinson disease (PD), the Berg Balance Scale (BBS), Forward Functional Reach Test (FFR), Backward Functional Reach Test (BFR), Timed “Up & Go” Test (TUG), and gait speed may be used to quantify some aspects of functional performance not measured by the UPDRS. The purpose of this study was to describe the relationship among a set of tests of balance, walking performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
72
0
15

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(98 citation statements)
references
References 32 publications
7
72
0
15
Order By: Relevance
“…The test has also revealed differences in performance between PD patients and healthy elderly subjects, and between PD patients in different phases of clinical fluctuation [28]. Supporting the results of Brusse et al [29], we found a high correlation between the TUGtest score and the UPDRS total score, motor and ADL subscores and the ÔbradykinesiaÕ score. Our results show a trend towards a worse performance in the TUG test and even more apparent difference in the walking speed between the fallers and non-fallers.…”
Section: Discussionsupporting
confidence: 89%
“…The test has also revealed differences in performance between PD patients and healthy elderly subjects, and between PD patients in different phases of clinical fluctuation [28]. Supporting the results of Brusse et al [29], we found a high correlation between the TUGtest score and the UPDRS total score, motor and ADL subscores and the ÔbradykinesiaÕ score. Our results show a trend towards a worse performance in the TUG test and even more apparent difference in the walking speed between the fallers and non-fallers.…”
Section: Discussionsupporting
confidence: 89%
“…Patients diagnosed with PD according to Parkinson's UK Brain Bank criteria 43 and Hoehn & Yahr stage 1-3 44 were recruited from the local health system. Volunteers enrolled in the study underwent neurologist evaluation to ensure PD diagnosis and to confirm the disease stage.…”
Section: Methods Participantsmentioning
confidence: 99%
“…Değerlendirme, 2. metrede bulunan çizgiyi aşan ilk adımdan itibaren başlamakta ve 8. metreyi aşan ilk adımda bitirilmektedir. Sonuç metre/saniye (m/ sn) şeklinde kaydedilmektedir (33,34).…”
Section: Kullanılan öLçeklerunclassified